Ethical Conflicts in Nursing: Concept, Current Situation, Causes and Influencing Factors - Yongmei, Hou (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Ethical conflicts are a common psychological problem in nursing work, which can significantly impact nurses’ mental health and the nursing profession’s development. Objective: The objective of the study is to understand the current situation and causes of ethical conflicts in nursing, and analyze the main influencing factors. Methods: The literature retrieval method was used to review empirical papers published in English or Chinese in the past 11 years in Google Scholar, PubMed, CNKI, and the Wanfang database. Results: Thirty-eight articles were included. The ethical conflicts in nursing are a multi-dimensional and multi-category concept that weakens nurses' mental health, reduces their job engagement, job effectiveness, and subjective well-being, and hinders the healthy development of the nursing profession. The most common causes of ethical conflicts were conflicts with physicians, inadequate staffing, and lack of autonomy. Conclusion: This study highlights the need for nursing educators, administrators, and policymakers to address the causes of ethical conflicts and develop strategies to mitigate their impact. Future research should focus on developing more robust tools and exploring the experiences of nurses from diverse backgrounds.